The Influence of Open and Distance Learning (ODL) on Students’ Innovative Behaviour: The Mediating Role of Creative-Self-Efficacy - Mustapa, Zuhaina; Omar, Muhamad Khalil; Abdullah, Dayang Nailul Munna Abg; Aluwi, Ainie Hairianie; Dahalan, Noor Azura (Advances in Social Sciences Research Journal, 2023)
The pandemic of Covid-19 that has attacked the world since December 2019 brought a reformation to the landscape of the higher-education institutional system in Malaysia. The Ministry of Higher Education has introduced Open and Distance Learning (ODL) on March 2020 as a new learning platform. ODL is a technology-based approach to supersede physical classrooms to enable continuity of learning during the Covid-19 pandemic era. ODL is a teaching and learning technique that fully employs the utilisation of the internet to enable the success of learning activities. ODL enable students to interact with lecturers and classmates, attend online classes, and access an abundance of knowledge and information available on the internet. Further, the application of the internet and technologies will promote students’ capacity to be more resourceful, knowledgeable, creative and innovative in the subject learned. The use of the ODL methods will enhance students’ innovative behaviour through the generation and implementation of ideas in students’ learning tasks. However, the ability of the students to learn from the internet and produce innovative behaviour is depending on their self-believability to be creative. Research on the effectiveness and outcome of ODL approach on students’ innovative behaviour has yet to be established and requires further attention. This research is intended to investigate the influence of learning from ODL approach on students’ innovative behaviour. Therefore, this research will also investigate the mediating effects of creative self-efficacy in the relationship between learning from ODL and innovative behaviour. This research is quantitative research, where data will be collected using questionnaires. The research data will be analysed using SPSS. The scope of this study is students of UiTM Cawangan Selangor who are now undergoing ODL classes. This research will be able to contribute to the body of knowledge and ignite light on the outcome of the ODL on students’ innovative behaviour.